Supporting Caregiver Use of Child Restraints in Rural Communities via Interactive Virtual Presence. (April 2020) - Swanson, Marissa; MacKay, Morag; Yu, Sophie; Kagiliery, Alexis; Bloom, Koren; Schwebel, David C.
When used correctly, child restraint systems (CRS) effectively reduce the risk of serious injury and death to child passengers in motor vehicle crashes. However, error rates in CRS use among caregivers are extremely high. Consultation with child passenger safety technicians (CPST) reduces misuse rates, but access to CPST is limited, particularly in rural areas. Remote consultation via interactive virtual presence (IVP) may increase access to CPST. One hundred and fifty caregivers in Southeast Montana completed remote consultation with CPST via IVP. Errors in CRS selection, installation, and child positioning were coded at baseline and postintervention in a within-subjects, pretest–posttest design. The proportion of caregivers making one or more errors in CRS selection (McNemar's test p < .001) and installation (McNemar's test p < .001), but not child positioning, significantly decreased following remote consultation. IVP is a promising mobile health (mHealth) strategy for providing remote consultation with CPST to improve rates of correct CRS use and mitigate child injury risk.